Do Complicated Tax Systems Prevent Foreign Direct Investment?. (28th June 2012) - Lawless, Martina
<x xml:space="preserve">Abstract</x> The negative relationship between tax rates and FDI is well known. This paper looks at how complexity of the tax system affects FDI. Fulfilling tax requirements can be time‐consuming, and this implies a cost for more complex tax systems. Alternatively, complexity may provide opportunities to reduce the overall tax bill. We find that measures of tax complexity have a significant inhibiting effect on the presence of FDI for a country pair, but have little impact on the level of FDI flows. A 10% reduction in tax complexity is comparable to a one percentage point reduction in effective corporate tax rates.